Improving State Estimation Accuracy Through Incremental Meter Placement Using New Evolutionary Strategy - Rosli, H.M.; Mokhlis, Hazlie; Naidu, K.; Jamian, J.J.; Bakar, Ab Halim Abu (Springer Verlag (Germany), 2014)
Power system network is an interconnected web of crucial electrical elements and system monitoring. It is imperative in ensuring system integrity and stability. In regard to this, state estimation is commonly employed to obtain the best estimate of the power system condition based on limited number of measurements. The placement of meters at appropriate locations is crucial in determining the accuracy of the state estimation. Hence, this paper presents a new optimal meter placement strategy for state estimation. A new evolutionary strategy for discrete optimization problem is proposed so that the location of additional meter placement will improve the accuracy of state estimation. The minimization of sum covariance error of state estimation is selected as the objective function to be minimized. Simulation results on the IEEE 30-bus system clearly shows that the proposed approach is able to outperform the conventional heuristic method in determining the optimal meter placement, which enhances the state estimation accuracy.